Mature Ovarian Teratoma with Carcinoid Tumor in a 28-Year-Old Patient - Stamatios Petousis; Ioannis Kalogiannidis; Chrysoula Margioula-Siarkou; Alexandros Traianos; Dimosthenis Miliaras; Apostolos Kamparoudis; Apostolos Mamopoulos; David Rousso (Case Reports in Obstetrics and Gynecology)
Introduction. Coexistence of carcinoid tumor inside a mature cystic teratoma is an extremely rare phenomenon, especially in young women. We present the case of a 28-year-old woman diagnosed with a right ovarian carcinoid and treated uneventfully with conservative surgical approach. Case Report. A 28-year-old woman, gravid 0, parity 0, presented to our department for her annual gynecological examination and Pap smear test. During her examination, a mobile cystic mass was detected in the right lower abdomen. Ultrasound indicated a right ovarian mass 10.5 × 6.3 cm, confirmed by CT scan. Further investigation revealed AFP levels (1539 ng/mL). The ovarian mass was excised by laparoscopy, leaving intact the remaining right ovary. Frozen sections showed a mature cystic teratoma. However, paraffin sections revealed the presence of a small carcinoid within the teratoma’s gastric-type mucosa. The patient was set to a close followup. Nine months postoperatively, ultrasound pelvis imaging and CT scan of the abdomen as well as serum tumor markers have shown no evidence of recurrence disease. Conclusion. Despite the weak evidence, fertility spare surgical approach for women wanting to preserve their genital tract might be a reasonable option.